Skuespillerfaget som lønarbejde og kønskonstruktion - Sjørup, Karen; Kirkegaard, Charlotte (Kvinder, Køn & Forskning, 2007)
The article is based on a survey concerning gender equality among artists in Denmark, conducted in 2007. It particularly focuses on the situation of actresses as modern, well-educated and gender equality conscious women, placed in a dilemma between their own desire to deconstruct and reconstruct images of gender in their work and the traditional, gender-stereotypical roles offered to them. They moreover are the victims of late working hours and low salaries, making it very difficult to maintain themselves financially and to live a life as independent working mothers. Ageing is also a very difficult bodily experience for the actresses, who will often be excluded and replaced by younger actresses. There is however a battle going on between the gender equality oriented actresses and the primarily male directors and instructors, in charge of allowing modernisation of gender roles in films and theatre. In sum, the article explores how gender is constructed culturally and how femininity might be reformulated to challenge heteronormative gender stereotypes.